2010
DOI: 10.1590/s1519-69842010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Diel and seasonal movements of grumatã Prochilodus lineatus (Valenciennes 1836) (Characiformes: Prochilodontidae) in the Sinos River, Southern Brazil

Abstract: Prochilodus lineatus is a reophilic migratory species of economical importance for local fisheries which is widely distributed in Brazil. The present study investigated diel and seasonal movement patterns, spawning migration and habitat use of P. lineatus in the Sinos River, Southern Brazil. Between August 2002 and March 2004, 19 grumatãs were tagged internally with digitally coded radio transmitters. Tracking was conducted weekly by boat or aircraft, and six fixed data loggers recorded movements of tagged fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Its reproductive habits are migratory, swimming upriver to spawn in the breeding season. The adults inhabit the main channel of the river, showing preference for river stretches surrounded by wetlands (Pesoa and Schulz, 2010). The young inhabit the marginal lagoons of the floodplain, where they remain during the first years of life (Agostinho and Júlio-Júnior, 1999;Graça and Pavanelli, 2007;Pesoa and Schulz, 2010).…”
Section: Species Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Its reproductive habits are migratory, swimming upriver to spawn in the breeding season. The adults inhabit the main channel of the river, showing preference for river stretches surrounded by wetlands (Pesoa and Schulz, 2010). The young inhabit the marginal lagoons of the floodplain, where they remain during the first years of life (Agostinho and Júlio-Júnior, 1999;Graça and Pavanelli, 2007;Pesoa and Schulz, 2010).…”
Section: Species Studiedmentioning
confidence: 99%
“…The adults inhabit the main channel of the river, showing preference for river stretches surrounded by wetlands (Pesoa and Schulz, 2010). The young inhabit the marginal lagoons of the floodplain, where they remain during the first years of life (Agostinho and Júlio-Júnior, 1999;Graça and Pavanelli, 2007;Pesoa and Schulz, 2010). Prochilodus lineatus was chosen due to its ecological relevance, importance for fishing, and because is one of the most used native fish in stocking and repopulation.…”
Section: Species Studiedmentioning
confidence: 99%
“…Data about recapture of electronic tagged fish and return of transmitters by fishers has been reported in other biotelemetry projects in Brazil and ranged from 13 to 54% (Godinho and Kynard, 2006;Godinho et al, 2007;Hahn et al, 2011;Pesoa and Schulz, 2010), values that are greater than observed so far in the Xingu River. The return of transmitters is important because it not only makes it possible to reuse the tags in other fish, but also because fishers will provide information on the use of habitats beyond the limits of study area and after the transmitter battery runs out.…”
Section: Reporting On the Recapture Of Electronic Tagged Fish By Fishmentioning
confidence: 93%
“…In order to increase the offspring survival and to avoid intraspecific competition, some species displace kilometres and occupy specific habitats, with higher productivity and lower predator density (Schulz, Leal, 2012). Long spawning migration can occur in some fish groups, such as salmonids and large migratory fishes from Amazon and Paraná basins (Goulding, 1980;Winemiller, Jepsen, 1998;Antonio et al, 2007;Fernadez et al, 2007;Pesoa, Schulz, 2010;Tejerina-Garro, Mérona, 2010). Fish movements in streams can also be important for the fish community stability (Martin-Smith et al, 1999).…”
Section: Original Articlementioning
confidence: 99%